Quality Indicators for the Diagnosis and Management of Menière's Disease. Issue 8 (September 2021) - Cottrell, Justin; Yip, Jonathan; Agrawal, Sumit; Archibald, Jason; Chau, Justin; Lea, Jane; Lin, Vincent; Mick, Paul; Morris, David; Parnes, Lorne; Schramm, David; Chan, Yvonne; et al.
Abstract : Objective: Menière's disease (MD) is a clinical disorder that often provides challenges in diagnosis and management. High-quality evidence to guide care providers is sparse, which can result in significant practice variations. Quality indicators (QIs) are one method that can be used to standardize and measure accepted care practices to improve healthcare quality and patient outcomes. Here, we developed practical, high-yield QIs that serve to measure and inform the quality of care provided to patients with MD. Study Design: Modified RAND Corporation University of California, Los Angeles appropriateness methodology for QI development. Setting: Multicenter nine-member expert panel. Patients: NA. Interventions: NA. Main Outcome Measure: Final QIs deemed appropriate measures of quality care with agreement by the expert panel. Results: Twenty-seven candidate indicators were identified after literature review. After the first round of evaluations, the panel agreed on three candidate indicators as appropriate QIs. A subsequent expert panel meeting provided a platform to discuss disagreements. Two agreed-upon QIs were revised during this discussion before final evaluations. The expert panel ultimately agreed upon five QIs as appropriate measures of high-quality care after completing final evaluations and reviewing updated literature. The five quality indicators measure audiometric documentation, minimization of electrocochleography, use of intratympanic dexamethasone, use of intratympanic gentamycin, and rate of labyrinthectomy/vestibular neurectomy in refractory MD patient. Conclusions: This study proposes five QIs that cover key aspects of care for MD, such as accurate diagnosis and management options including initial destructive therapies. These QIs can serve multiple purposes, the most important of which is to galvanize quality improvement initiatives.